Experimental warming increases fungal alpha diversity in an oligotrophic maritime Antarctic soil - Newsham, Kevin K.; Misiak, Marta; Goodall-Copestake, William P.; Dahl, Malin Stapnes; Boddy, Lynne; Hopkins, David W.; Davey, Marie L. (Frontiers in Microbiology, 2022)
The climate of maritime Antarctica has altered since the 1950s. However, the effects of increased temperature, precipitation and organic carbon and nitrogen availability on the fungal communities inhabiting the barren and oligotrophic fellfield soils that are widespread across the region are poorly understood. Here, we test how warming with open top chambers (OTCs), irrigation and the organic substrates glucose, glycine and tryptone soy broth (TSB) influence a fungal community inhabiting an oligotrophic maritime Antarctic fellfield soil. In contrast with studies in vegetated soils at lower latitudes, OTCs increased fungal community alpha diversity (Simpson’s index and evenness) by 102–142% in unamended soil after five years. Conversely, OTCs had few effects on diversity in substrate-amended soils, with their only main effects, in glycine-amended soils, being attributable to an abundance of Pseudogymnoascus. The substrates reduced alpha and beta diversity metrics by 18–63%, altered community composition and elevated soil fungal DNA concentrations by 1–2 orders of magnitude after five years. In glycine-amended soil, OTCs decreased DNA concentrations by 57% and increased the relative abundance of the yeast Vishniacozyma by 45-fold. The relative abundance of the yeast Gelidatrema was reduced by 78% in chambered soil and was increased 1.9-fold in irrigated soil. DNA concentrations were also halved by irrigation in TSB-amended soils. In support of regional- and continental-scale studies across climatic gradients, the observations indicate that soil fungal alpha diversity in maritime Antarctica will rise as the region warms, and help to explain why experimental warming does not consistently increase fungal community diversity in vegetated soils at lower latitudes.